Can detox nutrition be an adjunct in the treatment and rehabilitation of patients infected with the COVID-19 virus? - T. L. Pilat; A. V. Istomin; E. A. Gordeeva; R. A. Khanferyan (Лечащий Врач)
The article analyzes the rationale for the use and the results of the use of detoxification nutritional support in patients with COVID-19 viral infection. Data from a number of publications indicate that when infected with COVID-19, hemotoxic and metabolic effects occur, similar to those that occur with the accumulation of heavy metals. Intoxication of the body in coronavirus pathology is accompanied by violations of oxidative processes and overproduction, mainly of cytokines («cytokine storm»), which is largely due to a deficit in the consumption and accumulation of micronutrients and biologically active substances in the body with pronounced antioxidant, antiinflammatory, hepatoprotective and other activities ... The results of previous studies to assess the detoxification activity of the dietary food product suggested that this product may be effective in cases of intoxication caused by viral infections, in particular COVID-19 coronavirus. Thus, the use of jelly in a group of workers working in hazardous working conditions led to an increase in urinary excretion of nickel, copper and cobalt, an improvement in oxidative stress indicators: a decrease in malondialdehyde to 4,3 ± 0,06 μmol/l, increase in catalase activity from 417,2 ± 20,6 to 564,2 ± 20,1 μkat/L, superoxide dismutase from 13,7 ± 0,1 up to 15,3 ± 0,08 a.u., ceruloplasmin from 287,4 ± 6,1 to 331,2 ± 8,5 mg/ml. The obtained data, as well as knowledge about the peculiarities of the pathogenesis and course of COVID-19 infection, made it possible to include jelly in the maintenance therapy of patients with this disease. A survey of 283 people who have had a coronavirus infection showed the presence of symptoms of severe intoxication. Nutritional support for a month with detoxification jelly contributed to a significant reduction in symptoms of intoxication: weakness and fatigue, temperature fluctuations, fears, anxiety, suspiciousness, etc. disappeared. The authors recommend longer (at least 3-6 months) nutritional support by specialized detoxification food products for the full recovery of the body and further prevention of the development of post Сovid complications.